The idea of Pakistan - Cohen, Stephen P., 1936- (Brookings Institution Press, 2004)
In recent years Pakistan has emerged as a strategic player on the world stage ; both as a potential rogue state armed with nuclear weapons and as an American ally in the war against terrorism. But our understanding of this country is superficial. To probe beyond the headlines, Stephen Cohen, author of the prize-winning India: Emerging Power, offers a panoramic portrait of this complex country ; from its origins as a homeland for Indian Muslims to a militarydominated state that has experienced uneven economic growth, political chaos, sectarian violence, and several nuclear crises with its much larger neighbor, India. Pakistan's future is uncertain. Can it fulfill its promise of joining the community of nations as a moderate Islamic state, at peace with its neighbors, or could it dissolve completely into a failed state, spewing out terrorists and nuclear weapons in several directions? The Idea of Pakistan will be an essential tool for understanding this critically important country.